Bis‐Pyrene‐Modified Unlocked Nucleic Acids: Synthesis, Hybridization Studies, and Fluorescent Properties. Issue 9 (18th July 2014) - Perlíková, Pavla; Ejlersen, Maria; Langkjær, Niels; Wengel, Jesper
Abstract Efficient synthesis of a building block for the incorporation of a bis‐pyrene‐modified unlocked nucleic acid (UNA) into oligonucleotides (DNA*) was developed. The presence of bis‐pyrene‐modified UNA within a duplex leads to duplex destabilization that is more profound in DNA*/RNA and less distinct in DNA*/DNA duplexes. Nevertheless, the destabilization effect of bis‐pyrene‐modified UNA is weaker than that of unmodified UNA. Some oligonucleotides with bis‐pyrene‐modified UNA incorporations displayed superior mismatch discrimination capabilities. UV/Vis absorption and molecular modeling studies indicate that the pyrene groups of bis‐pyrene‐modified UNA are located in the major groove of a duplex. Oligonucleotides containing two bis‐pyrene‐modified UNA monomers showed low pyrene monomer emission in bulge‐containing duplexes, high pyrene monomer emission in fully matched duplexes, and 5‐(pyrenyl)uracil:pyrene exciplex emission in the single‐stranded form. Such fluorescent properties enable the application of bis‐pyrene‐modified UNA in the development of fluorescence probes for DNA/RNA detection and for detection of deletions at specific positions.